The problematic scope of extended confiscation in comparative perspective - Ochnio, Ariadna H. (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The scope of extended confiscation is determined, inter alia, by the choice of triggering offences in Directive 2014/42/EU of the European Parliament and of the Council of 3 April 2014 on the freezing and confiscation of instrumentalities and proceeds of crime in the European Union. The question arises whether EU law guarantees appropriate limits of extended confiscation considering its specificity and the growing range of application in national legal orders. The study compared the normative framework of extended confiscation adopted in the criminal law of Poland, Romania, Germany, Austria, France, Spain, Finland, the Netherlands, and England and Wales. The list of offences, relevant for the scope of extended confiscation, is to be assessed by the Commission by 4 October 2019. The conclusions of the study concern the need to introduce, at the level of EU law, adequate safeguards against the disproportionate application of extended confiscation.
Keywords: konfiskata rozszerzona; przepadek; korzyści z przestępstwa; przestępstwa zharmonizowane; proporcjonalność